Pengaruh Lingkungan Kerja dan Komunikasi terhadap Disiplin Karyawan di Restoran Cap Lapan Kuda Kota Blitar - Moh. Ridwan; Eko Adi Susilo; Anwar Hakim Darajat (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This research is a quantitative study to determine the influence of the work environment and communication on employee work discipline at the Cap Lapan Kuda restaurant, Blitar City. The research method used was the saturated sampling technique using the entire population as a sample with a total of 30 employees at the Cap Lapan Kuda restaurant, Blitar City. The results of this research state that work environment variables partially influence work discipline and communication does not partially influence work discipline. However, simultaneously the work environment and communication variables influence work discipline.